Long-stroke mechanisms with minimal side reaction in translational pair - P. D. Balakin; I. P. Zgonnik (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Long-stroke mechanisms with minimal side reaction in the translational pair are presented. The variants of technical solutions of long-stroke mechanisms that meet inconsistent criteria for minimization of both lateral reaction in the progressive pair and dimensions-mass characteristics are given. A promising solution has been proposed and recommendations on composition of geometric constraints in kinematic pairs has been developed. The proposed technical solutions are generally aimed at increasing the resource of long-stroke mechanisms